Comparism between Keratometric and Subjective Astigmatic Correction in a Black Population - Odjimogho, Emoefe Sunny; Odjimogho, Stella E. (Darul Yasin Al Sys, 2025)
This study was carried out to compare keratometric and subjective astigmatic corrections. The method involved the examination of one hundred (100) subjects aged between 16 – 35 years with mean age of 22.74±4.55. The sample population comprised of fifty (50) males and fifty (50) females who were all Astigmats and had no history of any systemic/ocular pathologies and ocular surgery. The subjective correction was determined with static retinoscopic and subjective refractive techniques using the Jackson cross cylinder (JCC). The keratometric measurement was done with the Bausch and Laumb (B&L) keratometer. The result obtained revealed that the observed mean Astigmatic reading with the B&L keratometer was -0.858±0.629 while that of subjective was -1.20±0.79, and there was a significant difference between the two methods (subjective and keratometric) using the paired t – test (t = 5.787, p < 0.05). There was no significant difference between keratometric or subjective readings (p>0.05) which implied that either of these two methods could be used to estimate patients astigmatic correction.